2011
DOI: 10.1007/s11262-011-0650-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic detection and analysis of porcine bocavirus type 1 (PoBoV1) in European wild boar (Sus scrofa)

Abstract: Novel porcine parvoviruses showing the genetic characteristics of bocaviruses have recently been identified. The first such porcine bocavirus (PoBoV1), described as boca-like virus (PBo-likeV), was discovered in PMWS affected pigs in Sweden. Later, several other bocaviruses with divergent genomes were reported under various names in domestic pigs. This is the first report of the presence of bocaviruses in European wild boars. 842 wild boar samples originating from the Western region of Romania (Transylvania) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Based on differences of PBoV NS1 gene, five gene groups (PBoV1–5) were divided as previous report [6, 15]. PBoV-a sequences have 91.7% to 99% identities with each other as well as about 95% identity with published PBoV3 sequences from Hong Kong (JX429834), USA (JF713715, JF713714) or UK (JF512472), and more, 92%–96% identity with PBoV4 sequences from Hong Kong (JF429835, 429836) [17]. PBoV-b had 2 Shandong isolate sequences (JX944658, JX944667) which gave match with PBoV3 JN681175.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on differences of PBoV NS1 gene, five gene groups (PBoV1–5) were divided as previous report [6, 15]. PBoV-a sequences have 91.7% to 99% identities with each other as well as about 95% identity with published PBoV3 sequences from Hong Kong (JX429834), USA (JF713715, JF713714) or UK (JF512472), and more, 92%–96% identity with PBoV4 sequences from Hong Kong (JF429835, 429836) [17]. PBoV-b had 2 Shandong isolate sequences (JX944658, JX944667) which gave match with PBoV3 JN681175.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that porcine parvovirus type 1 is a causative agent of reproductive failure in sows, while the pathogenicity of other types of Parvoviruses [6, 11, 19] and members of other genus such as Bocavirus or Covirus remain to be determined. Numerous experimental investigations reported that coinfection of PCV2 with other viruses can contribute to the development of the PMWS in pigs [17, 20, 21]. It needs to be confirmed by experiments whether it is the case for PBoV.…”
Section: Discussionmentioning
confidence: 99%
“…Individual infection of PBoV usually causes no apparent clinical signs, and the co-infection of PBoV could make the clinical signs more obvious (Kesebir et al, 2006). Many scientists have also reported that PBoV exhibit varying prevalence rates with a wide range from 1.5% to 88% in pig samples from different regions (Blomstrom et al, 2009(Blomstrom et al, , 2010Zhai et al, 2010;Cadar et al, 2011;Li et al, 2011;McKillen et al, 2011;Shan et al, 2011a;Zeng et al, 2011;Zhang et al, 2011). In the present manuscript, compared with other organs in Chinese samples, the spleen (20.8%) and inguinal lymph node (27.2%) have much higher positive rates, suggesting that they are organs in which PBoV replication likely easily takes place.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that PBo-likeV might also play a role in PMWS. PBo-likeV also was detected in 12.94% of Transylvanian wild boars [8], but beyond Europe, it has only been identified in China so far [27]. Thirtyone farms from nine Chinese provinces were examined from January to December in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other three HBoVs (HBoV2, HBoV3 and HBoV4) have been discovered in respiratory and enteric infections in humans [4,10,19,25]. A porcine boca-like virus (PBo-likeV) was described in Sweden, using random multiple displacement amplification (MDA) and largescale sequencing [6], and it was reported recently in wild boars in Romania [8]. Beyond Europe PBo-likeV has also been identified in China [27].…”
Section: Introductionmentioning
confidence: 99%